The Dynamics Study of Regulations on Syariah Banking Indonesia - Dr. Muhammad Arifin S.H., M.Hum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Syariah banking as a business entity, which becomes a part of the national banking system.